2003
DOI: 10.1292/jvms.65.363
|View full text |Cite
|
Sign up to set email alerts
|

A Long Term Comparison between Denacol EX-313-Treated Bovine Jugular Vein Graft and Ultrafine Polyester Fiber Graft for Reconstruction of Right Ventricular Outflow Tract in Dogs.

Abstract: ABSTRACT. A Denacol EX-313 (Denacol)-treated bovine venous graft and an ultrafine polyester fiber (UFPF) graft were transplanted as patch graft into the right ventricular outflow tract under extracorporeal circulation in six dogs each experimentally. Hemodynamics in right heart and histological findings around the graft were compared between both groups over a period of one year after grafting. Pressure measurements and angiocardiography were performed through a cardiac catheter. Right ventricular pressure, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A), suggesting potentially different mechanisms of healing in polyester and pericardial patches. Polyester is noncompliant compared to other commonly implanted vascular biomaterials, and accordingly may support less neoendothelialization …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A), suggesting potentially different mechanisms of healing in polyester and pericardial patches. Polyester is noncompliant compared to other commonly implanted vascular biomaterials, and accordingly may support less neoendothelialization …”
Section: Discussionmentioning
confidence: 99%
“…Polyester is noncompliant compared to other commonly implanted vascular biomaterials, and accordingly may support less neoendothelialization. [52][53][54][55] Smooth muscle cells play an important role in pathogenesis of neointimal hyperplasia. 56 In the neointima that forms on both venous and arterial patches, alpha-actin/MHC dual-positive cells were present with greater number of these cells in arterial compared to venous patches ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Dacron® is predominantly used as aortic and large diameter peripheral bypass grafts (< 6mm) with relative success. Other polyesters have also been used as grafts in aortic and heart repairs 20. In a preliminary study, silver‐coated polyester prostheses were employed in 27 cases of aortic graft infections.…”
Section: Prosthetic Bypass Graftsmentioning
confidence: 99%
“…Polyepoxy compounds reduce calcification, degeneration and thrombosis of biological tissue and have lower cross-linking cytotoxic reaction [17,22]. Previous studies reported the excellent durability of polyepoxy compound fixed bovine jugular vein graft for reconstruction of right ventricular outflow tract in dogs [15]. The canine aortic bioprosthetic valve was fixed in glutaraldehyde and an epoxy compound, and an apico-aortic valve conduit using the valve was found to be effective for surgical treatment of aortic stenosis in dogs [11].…”
Section: Discussionmentioning
confidence: 99%